Foraging height and landscape context predict the relative abundance of bird species in urban vegetation patches - SHANAHAN, D. F.; POSSINGHAM, H. P.; MARTIN, T. G. (Austral ecology, 2011)
In Australian urban environments, revegetation and vegetation restoration are increasingly utilized conservation actions. Simple methods that help assess the utility of urban vegetation for bird species will help direct this effort for bird conservation purposes. We therefore examine whether ecological principles can be used to predict, a priori, the relative abundance of different bird species in urban vegetation. Our model proposes that a bird species will be in greater abundance where vegetation structure better reflects its foraging height requirements, and this relationship will be moderated by the landscape context of the patch. To quantify and test this model, we created an index to rank existing and revegetated urban vegetation sites in order of greatest expected abundance for each of 30 bird species. We tested this model, alongside two simpler models which consider landscape context and foraging height preferences alone, using bird abundance data from 20 woodland remnants and 20 revegetated sites in Brisbane, Australia. From these bird abundance data, we calculated the relative abundance of each species between the top‐ranking sites and lowest‐ranking sites. The model which incorporated both foraging height requirements and landscape context made predictions that were positively correlated with the data for 77% of species in remnant vegetation and 67% in revegetation. The results varied across species groups; for example, we achieved lower predictive success for canopy foraging species in the less mature revegetation sites. Overall, this model provided a reasonable level of predictive accuracy despite the diversity of factors which can influence species occurrence in urban landscapes. The model is generic and, subject to further testing, can be used to examine the effect of manipulating vegetation structure and landscape context on the abundance of different bird species in urban vegetation. This could provide a cost‐effective tool for directing urban restoration and revegetation efforts.